Renal function after low central venous pressure‐assisted liver resection: assessment of 2116 cases. Issue 3 (11th November 2014) - Correa‐Gallego, Camilo; Berman, Alexandra; Denis, Stephanie C.; Langdon‐Embry, Liana; O'Connor, David; Arslan‐Carlon, Vittoria; Kingham, T. Peter; D'Angelica, Michael I.; Allen, Peter J.; Fong, Yuman; DeMatteo, Ronald P.; Jarnagin, William R.; et al.
Abstract Objectives Low central venous pressure (LCVP)‐assisted hepatectomy is associated with decreased blood loss and lower transfusion rates. Concerns about its impact on renal function have prevented widespread application. This study was conducted to review the dynamics of renal function after LCVP‐assisted hepatectomy. Methods A retrospective analysis of a prospective surgical database was carried out. Estimated glomerular filtration rate (eGFR) was calculated using the Modification of Diet in Renal Disease (MDRD) equation. The RIFLE (risk–injury–failure–loss–end‐stage) criteria were used to define postoperative biochemical acute kidney injury (bAKI). Occurrences of clinically relevant AKI (cAKI) were identified in the study center postoperative database. Results During the period 2003–2012, 2116 LCVP‐assisted hepatectomies were performed. The median patient age was 61 years [interquartile range (IQR): 51–70 years] and 51% of patients were male. The median number of resected segments was two; resections involved from one to four segments. Median estimated blood loss was 300 ml (IQR: 200–600 ml). Rates of morbidity and 90‐day mortality were 21% and 2%, respectively. Low baseline eGFR (<90 ml/min) was seen in 84% of patients; 29% of patients had eGFR of <30 ml/min. Postoperative bAKI was seen in 17% (n = 350) of patients. Biochemical AKI with low eGFR was seen in 336 patients, representing 16% of the whole cohort; 13% of patients had been at risk, 2% experienced injury and 1% experienced failure. Kidney function had normalized at discharge in 159 of these patients. Nine patients (<1%) developed postoperative cAKI. Conclusions The majority of patients in the study cohort had low baseline eGFR. Biochemical alterations in eGFR are transient in the vast majority of patients after LCVP‐assisted hepatectomy and their clinical impact is limited. The present data suggest that clinically relevant renal dysfunction is a very uncommon event in patients undergoing LCVP‐assisted liver resection.